2013
DOI: 10.1185/03007995.2013.860019
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, patient satisfaction, and perceptions of post-surgical pain: results from a US national survey

Abstract: Objective: During the past two decades, professional associations, accrediting bodies, and payors have made postsurgical pain treatment a high priority. In light of the disappointing findings in previous surveys, a survey was conducted to assess patient perceptions and characterize patient experiences/levels of satisfaction with post-surgical pain management. Research design and methods:Survey included a random sample of US adults who had undergone surgery within 5 years from the survey date. Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
480
7
33

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 693 publications
(529 citation statements)
references
References 13 publications
9
480
7
33
Order By: Relevance
“…Despite increased awareness and clinical advancements, however, there has been limited improvement in control of post-surgical pain. 15 A recent study found that more than 80% of patients still experience pain after surgery, and 75% of those have moderate to extreme pain in the immediate postoperative period. It is therefore hardly surprising that post-surgical pain is the patient's greatest concern before surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite increased awareness and clinical advancements, however, there has been limited improvement in control of post-surgical pain. 15 A recent study found that more than 80% of patients still experience pain after surgery, and 75% of those have moderate to extreme pain in the immediate postoperative period. It is therefore hardly surprising that post-surgical pain is the patient's greatest concern before surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore hardly surprising that post-surgical pain is the patient's greatest concern before surgery. 15 Hence, there is paramount importance in harnessing multimodal techniques to achieve effective analgesia. With an emphasis on multimodal analgesia, this review covers techniques to optimize pain management and thus facilitate enhanced post-surgical recovery.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Less than half of patients who undergo surgery report adequate post-operative pain relief. 24 Inadequately controlled pain negatively affects quality of life (QoL), function, functional recovery, the risk of post-surgical complications, and the risk of persistent postsurgical pain.…”
Section: Approach To Post-operative Pain Management In Non-opioid Usementioning
confidence: 99%
“…Net 75 proc. iš jų skausmą apibūdina kaip vidutinio sunkumo, sunkų ar nepakeliamą [1,2]. Šios studijos patvirtina, kad šis pooperacinis skausmas vis dar yra gydomas netinkamai.…”
Section: įVadasunclassified